Meningkatkan Ketahanan Pangan Sebagai Upaya Pencegahan Stunting di Desa Beka - Syafutra, Rafik Priyadi; Rafika, Ika; Adda, Harnida Wahyuni (Universitas Gajah Putih, Indonesia, 2023)
Stunting is condition child short from his age at cause by lack energy cornice in long time . Lack nutrition on baby can happen started from in content until baby 2 years old . After baby 2 years old incident new stunt can seen . Land clearing aims to increase food security as an effort to prevent stunting in Beka Village with a method that includes several stages according to the functions of management, planning, organizing, actuating and controlling. Based on the results of the programs that have been implemented, it can be seen that the problem that occurred before the opening of the sixteen additional food security lands was the non-fulfillment of the food needs of the people of Beka Village. Food security is an important element in preventing stunting. Therefore it is felt necessary to increase food security by opening additional land specifically for food supplies (vegetables) to maintain food security in order to prevent stunting and improve the welfare of the people of Beka Village.